Firm's financial risk vulnerability: evidence from Nigeria. (2017) - Asien, Etumudon Ndidi
This paper examines mean differences in working capital items (liquidity ratio, quick ratio, cash ratio and cash conversion days) and financial leverage of at-risk and not-at-risk firms. The paper also examines association between working capital items and financial leverage. Four hypotheses are tested using data from 2015 online annual financial statements of 89 quoted firms from ten industry sub-sectors classified by the Nigerian Stock Exchange. The data were analysed using paired samples t-tests and OLS multiple regressions. T-test results suggest that there are significant differences in working capital items and financial leverage of not-at-risk and at-risk firms. Comparisons of at-risk and not-at-risk firms suggest that, except for cash ratio, the association between working capital items and financial leverage is not equal for the two groups of firms. Result from the pooled sample suggests that working capital items are significantly associated with financial leverage. The results are not sensitive to industry membership. The pooled model, not-at-risk model and at-risk model explains, respectively, about 67%, 31%, and 94.7% of the variation in financial leverage. The paper recommends that even though firms have enough cash they could still borrow to augment their capital structure.